Masturbasi Dalam Perspektif Ibn Hazm Dan Imam Asy-Syafi’i - Rijal Nurdin; Siti Syahidah; Devi Marliana Putri; Norhani Aminah; M Luthfi Setiarno (Jurnal Media Informatika, 2025)
This article aims to analyze the legal status of masturbation from the perspectives of two prominent Islamic scholars: Ibn Hazm and Imam Al-Shafi’i. It presents the differing views of these scholars along with the arguments underlying their opinions. Masturbation, as an individual sexual behavior, has become a significant issue in contemporary Islamic jurisprudence, particularly in light of the rapidly evolving social and moral context of Muslim communities. Until today, masturbation has triggered various scholarly debates, with some jurists prohibiting it while others permit it under specific circumstances. This study employs a library research method using a normative-descriptive and analytical approach. The data used were obtained from primary sources, such as classical fiqh texts and scholarly works, as well as secondary sources including relevant academic publications. The findings reveal that Ibn Hazm allows masturbation in certain situations as a means to prevent adultery, while Imam Al-Shafi’i prohibits it except in cases of necessity. Both perspectives are essential for understanding the flexibility of Islamic jurisprudence in addressing contemporary issues. This article also discusses the factors and motivations behind masturbation, along with Sharia-based solutions to prevent it. The study concludes that understanding the social and psychological aspects is crucial in applying Islamic law in the domain of human sexuality.